Analysis of heavy metal pollution of chromium (Cr) and nickel (Ni) in soil at Putri Cempo Landfill, Indonesia - Rachmawati Siti; Hawali Abdul Matin Hashfi; Khoiriyah Azzam Atikah; Meilana Arifiandita Dio; Darma Nurcahyo Furqon; Hamonangan Manullang Raymond; Susatio Raja (BIO Web of Conferences)
Putri Cempo Landfill uses open dumping which can increase the risk of soil pollution due to heavy metals. Heavy metal contamination is a critical issue because it negatively impacts human health and causes environmental damage that can threaten the sustainability of the economy and ecosystems at a global level. This study aims to analyse the current conditions regarding the concentration of heavy metals in the soil at Putri Cempo Landfill with the parameters of heavy metals Cr and Ni and to determine the impact of these heavy metals on human health. Analysis of Cr and Ni content was carried out using Atomic Absorption Spectrophotometry (AAS). Data analysis was carried out by comparing the content of heavy metals in the soil at Putri Cempo Landfill with the SNI on the Threshold Limit Value (NAB) of Heavy Metals in Sediment/Soil. The results of laboratory tests showed that there was a content of heavy metals Cr of 1.2279 mg/L and Ni of 0.94842 mg/L. It can be concluded that with the Cr and Ni content, the soil at Putri Cempo Landfill has exceeded the limits set by SNI so that it can be considered contaminated by heavy metals Cr and Ni. This finding points to the need for mitigation to reduce health and environmental risks. It is recommended to enhance public education, improve waste management, implement remediation techniques, and regularly monitor air and soil quality. These steps can protect health and reduce the long-term impact of pollution if carried out sustainably.